2021
DOI: 10.3389/fvets.2021.668120
|View full text |Cite
|
Sign up to set email alerts
|

A Multiomic Approach to Investigate the Effects of a Weight Loss Program on the Intestinal Health of Overweight Horses

Abstract: Obesity is endemic in human populations in the western society, and with mounting evidence that the intestinal ecological environment plays a major role in its pathogenesis, identification of therapies based on intestinal microbiota modulation are gaining attention. Obesity in companion animals is also a common clinical problem. We set out using a multidimensional approach, to determine the effectiveness and safety of a weight loss program for horses incorporating diet restriction and exercise. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 90 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…Meanwhile, some beneficial microbes in the gut can also specifically bind to the mucosal epithelium to enhance the gut immune protection barrier, thus preventing the invasion of pathogenic microorganisms ( 3 ). In addition to nutritional and immune barrier roles, the composition of the gut microbiota and their stability also play an important role in the host behavior ( 4 ), metabolism ( 5 ), obesity ( 6 ), disease ( 7 ), and more.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some beneficial microbes in the gut can also specifically bind to the mucosal epithelium to enhance the gut immune protection barrier, thus preventing the invasion of pathogenic microorganisms ( 3 ). In addition to nutritional and immune barrier roles, the composition of the gut microbiota and their stability also play an important role in the host behavior ( 4 ), metabolism ( 5 ), obesity ( 6 ), disease ( 7 ), and more.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies conducted in various animal models met the inclusion criteria for this review ( Table 2 ). Of these 13, 5 were conducted in mice (Lamoureux et al, 2017; Houghton et al, 2018; Ribeiro et al, 2019; Chen et al, 2021; Yang et al, 2021a), 4 were in rats (Mika et al, 2015; Giacco et al, 2020; Meng et al, 2020; Castro et al, 2021), and 4 in horses (De Almeida et al, 2016; Janabis et al, 2016; Janabi et al, 2017; Walshe et al, 2021). All but one (Castro et al, 2021) of these studies examined the effects of either aerobic exercise or interventions with aerobic exercise as an important component.…”
Section: Resultsmentioning
confidence: 99%
“…All but one (Castro et al, 2021) of these studies examined the effects of either aerobic exercise or interventions with aerobic exercise as an important component. Twelve studies were trials with a parallel design (2–8 arms) (Mika et al, 2015; De Almeida et al, 2016; Janabis et al, 2016; Lamoureux et al, 2017; Houghton et al, 2018; Ribeiro et al, 2019; Giacco et al, 2020; Meng et al, 2020; Castro et al, 2021; Chen et al, 2021; Walshe et al, 2021; Yang et al, 2021b), of which the longest trial had a duration of 7 mon (Houghton et al, 2018) and the shortest trials had a duration of 3 days (Giacco et al, 2020). One study followed a crossover design in which horses were exposed to a graded exercise test and a standing control (Janabi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a growing health issue in horses, as it is linked to metabolic disorders like insulin imbalances, high lipid levels, and laminitis [113][114][115]. Studies have shown that gut microbiota can change in overweight horses after weight loss [116], leading to a significant increase in the alpha-diversity of their fecal microbiota. Given these findings and the impact gut microbiomes have on fitness, using lean horse feces, selected based on Body Condition Score (BCS), as a treatment option for weight loss in overweight horses may be a safe and cost-effective approach.…”
Section: Future Prospectivementioning
confidence: 99%